How effective are retargeting ads? - Rodrigues, T. (2021)
Although nowadays people tend to avoid advertising, retargeting has proven to be a very successful method for bringing back consumers and help them on their final decision. However, research on attention to retargeted campaigns have been scarce. In the current study, a longitudinal experiment was used to study participants reactions to different types of advertising – retargeted, targeted and generic –and how retargeted adverts impact their intention to revisit the website, purchase and recommend. An eye-tracker measured attention to the different types of advertising and emotions were measured as mediators. This study shows that retargeted advertising gets higher levels of attention than the other two types of ads. Also, it was possible to understand that retargeted advertising has a positive direct relationship with intention to revisit, and a positive indirect relationship with intention to purchase and intention to recommend, both mediated by intention to revisit.